The Relationship Of Knowledge About Sexually Transmitted Infections With Premarried Sex Attitude In Adolescent In The Environment Iii Bamboo Field New Neighborhood - Suriati Lubis; Sari Fitri (Science Midwifery, 2020)
Sex that is done freely and haphazardly is at risk of bringing STDs (Sexually Transmitted Diseases). STDs are transmitted due to the exchange of fluids in the body with the sufferer, one of which is the entry of the male penis into the female vaginal opening or by touching the skin. This study aims to determine the relationship between knowledge about sexually transmitted infections and premarital sex attitudes in adolescents in Environment III Kelurahan Baru Ladang Bambu. This research method usesobservationalanalyticwith a cross-sectional approach method. Where the population is teenagers as many as 30 people and the sample is 30 people. The results of the analysis showed that of the 30 teenagers, the majority there were 23 people (76.7%) with less knowledge and the minority with good knowledge 3 people (10%). Adolescent attitudes towards premarital sex were negative 23 people (76.7%) and 7 people (23.3%) were positive. The results of the Chi-Square test obtained a value of = 0.053, this means that the p-value is greater than (0.05), which means that there is no relationship between knowledge about sexually transmitted infections and premarital sex attitudes in adolescents. It is hoped that teenagers in Environment III Kelurahan Baru Ladang Bambu will further increase their knowledge about sexually transmitted infections.